A real-time processing application for topographical surveying tested in coffee production area - Silveira, Pedro David Netto; Mendes, Vinício Fragoso; Ferrari, Jéferson Luiz (Coffee Science - ISSN 1984-3909, 2017)
The breakthrough in application development for mobile devices, such as smartphones, has enabled farmers to gather and store data and information about his properties and crops. This work’s objective is the development of a mobile application with real-time processing to topographical survey that helps the coffee producer and other farmers register the geographical location and calculate the area and perimeter of a region delimited on the terrain. The application, called Calc-Geo, was developed for the Android platform and interfaces the smartphone’s GNSS receivers. The information quality generated by Calc-Geo was tested in two experiments. First, the Calc-Geo was used to capture geographic coordinates of a geodesic landmark in the Espírito Santo state in order to determine the GNSS receivers positional accuracy. Later, the Calc-Geo was employed in the altimetry-plane survey of a coffee crop field. The area and the perimeter of this crop were compared with a total station surveying results. The discrepancies analysis showed that, on average, there is a positional deviation of 1.17 m and a difference smaller than 1% in the crop perimeter and area values. This application is an attractive alternative technology, because the farmer would not need to acquire specific GPS receivers for data collecting and then perform the processing. Among other features, the Calc-Geo allows field registering, determines distance between two geographical points and sends collected data by mobile phone with intent of integration with other technologies.